2020
DOI: 10.1101/2020.06.30.20143867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROX Index Predicts Intubation in Patients with COVID-19 Pneumonia and Moderate to Severe Hypoxemic Respiratory Failure Receiving High Flow Nasal Therapy

Abstract: Introduction Use of high flow nasal therapy (HFNT) to treat COVID-19 pneumonia has been greatly debated around the world due to concern for increased healthcare worker transmission and delays in invasive mechanical Ventilation (IMV). Methods A retrospective analysis of consecutive patients admitted to Temple University Hospital in Philadelphia, Pennsylvania, from March 10, 2020, to May 17, 2020 with moderate to severe respiratory failure treated with High Flow nasal therapy (HFNT). HFNT patients were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Next, we compared the molecular approach (measuring a biomarker like CRP) with a physiological approach (calculating the ROX index, an established clinical scoring system for predicting intubation). 11 The ROX index incorporates oxygenation and respiratory rate, specifically oxygen saturation divided by fraction of inspired oxygen divided by respiratory rate (i.e., [SpO 2 /FiO 2 ]/RR). Thus, the ROX index integrates hypoxemia and “work of breathing.” The AUC for ΔCRP was greater than that for the ROX indices on day 0 and day 1 (0.68 [0.51–0.85] and 0.71 [0.58–0.83], respectively; Figures 3 F and 3G).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we compared the molecular approach (measuring a biomarker like CRP) with a physiological approach (calculating the ROX index, an established clinical scoring system for predicting intubation). 11 The ROX index incorporates oxygenation and respiratory rate, specifically oxygen saturation divided by fraction of inspired oxygen divided by respiratory rate (i.e., [SpO 2 /FiO 2 ]/RR). Thus, the ROX index integrates hypoxemia and “work of breathing.” The AUC for ΔCRP was greater than that for the ROX indices on day 0 and day 1 (0.68 [0.51–0.85] and 0.71 [0.58–0.83], respectively; Figures 3 F and 3G).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, all patients with a ROX>4.88 were less likely to be intubated 4. A retrospective study involving 129 COVID-19 patients investigating the use of ROX index, confirmed the validity of this simple tool to predict need for intubation 17.…”
mentioning
confidence: 73%
“…It was found that anticoagulation is associated with lower intubation [37]. The result of a study suggests that the ROX index is a noninvasive and outstanding predictor for the necessity of intubation in COVID-19 patients [51]. The ROX index is the ratio of oxygen saturation as measured by pulse oximetry/FiO2 to respiratory rate, it is assessed as a predictor of the need to intubate in patients who received high flow nasal cannula oxygen therapy [52].…”
Section: Discussionmentioning
confidence: 99%